Organobismuth Reagents: Synthesis, Properties and Applications in Organic Synthesis - Gagnon, Alexandre; Dansereau, Julien; Le Roch, Adrien (Synthesis, 2017)
Organobismuth compounds are organometallic reagents that contain a C–Bi bond. These species, which are easily accessed from inexpensive and low-toxicity inorganic bismuth salts, are highly attractive in synthesis due to their unique properties and reactivity. A wide diversity of geometries have been found for organobismuth compounds, depending on the oxidation state of the bismuth, its charge, and the number of coordinated elements. Compounds where the bismuth bears a –1 charge (organobismuthate), a +1 (bismuthonium cation) and a +2 charge (bismuthonium dication) have been reported. Due to the presence of a lone pair, trivalent organobismuthines can act as Lewis bases in transition-metal complexes. In addition, organobismuth compounds can act as Lewis acids by forming hypervalent interactions with ligands and metals. Organobismuth compounds have been used as catalysts and reagents in a plethora of reactions. In this review, the synthesis and properties of organobismuth reagents and their use in organic reactions are reviewed.1 Introduction2 Synthesis of Trivalent Organobismuthines3 Synthesis of Pentavalent Organobismuth Compounds4 Structure, Hypervalency and Chirality5 C-, N-, O- and S-Arylation Reactions6 Palladium-Catalyzed Reactions7 Other Reactions Involving Organobismuth Reagents8 Conclusion
Keywords: organobismuth compounds; hypervalency; chirality; arylation reactions; cross-coupling reactions; metal-catalyzed reactions